2021
DOI: 10.1021/acsami.1c05669
|View full text |Cite
|
Sign up to set email alerts
|

Albumin-Templated Bi2Se3–MnO2 Nanocomposites with Promoted Catalase-Like Activity for Enhanced Radiotherapy of Cancer

Abstract: Novel and effective radiosensitizers that can enhance radiosensitivity of tumor tissues and increase the local radiation dose are highly desirable. In this work, templated by bovine serum albumin (BSA), Bi2Se3–MnO2 nanocomposites (Bi2Se3–MnO2@BSA) were fabricated via biomineralization, while Bi2Se3 nanodots act as radiosensitizers to increase the local radiation dosage because of their strong X-ray attenuation ability, and MnO2 with catalase-like activity can increase the oxygen concentration in tumors by trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 52 publications
(84 reference statements)
0
24
0
Order By: Relevance
“…79 Bi-containing semiconductors such as Bi 2 S 3 , Bi 2 Se 3 and Bi 2 O 3 have the advantages of small carrier effective masses, long Fermi wavelength, and small band overlap energy, are popular materials in the field of radiosensitization. [80][81][82][83] In addition, studies have shown that Bi is not only an excellent photothermal material, but can also be used for computed tomography (CT) as a radiosensitizer and a contrast agent. 84 Bi-based nanomaterials could utilize the high-Z element Bi to block X-rays and interact with and deplete GSH, thereby increasing X-ray deposition at tumor sites and enhancing RT.…”
Section: Semiconductor Metal-based Nanoradiosensitizersmentioning
confidence: 99%
See 2 more Smart Citations
“…79 Bi-containing semiconductors such as Bi 2 S 3 , Bi 2 Se 3 and Bi 2 O 3 have the advantages of small carrier effective masses, long Fermi wavelength, and small band overlap energy, are popular materials in the field of radiosensitization. [80][81][82][83] In addition, studies have shown that Bi is not only an excellent photothermal material, but can also be used for computed tomography (CT) as a radiosensitizer and a contrast agent. 84 Bi-based nanomaterials could utilize the high-Z element Bi to block X-rays and interact with and deplete GSH, thereby increasing X-ray deposition at tumor sites and enhancing RT.…”
Section: Semiconductor Metal-based Nanoradiosensitizersmentioning
confidence: 99%
“…As shown in Fig. 4, Yao et al 80 used bovine serum albumin as a template to prepare Bi 2 Se 3 –MnO 2 nanocomposites. The nanocomposites were used as radiosensitizers to increase the local radiation dose, and showed excellent performance in CT and MRI.…”
Section: Semiconductor Metal-based Nano-radiosensitizersmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 20 ] Second, it can effectively alleviate hypoxia of TME by decomposing intracellular H 2 O 2 to O 2 , showing catalase‐like activities. [ 49 ] To verify this point, dissolved O 2 content increment in real‐time of two samples is detected in PBS solution containing 5 × 10 −4 m H 2 O 2 under US irradiation (Figure 2f ). After 200 s incubation, the dissolved O 2 content increment of MO@FHO reaches 8.5 mg L −1 , about 1.5 times of that of MO (5.7 mg L −1 ).…”
Section: Resultsmentioning
confidence: 92%
“…Herein, we provide the BSA-templated MnCO 3 nanoparticles (denoted as MnCO 3 @ BSA) through biomineralization procedure, in which BSA serves as scaffolds for nanoparticle growth and minimizes the toxicity. 23,24 After intravenous injection, the as-prepared MnCO 3 @ BSA nanoparticles preferentially accumulated into the infarcted regions of heart, therefore providing a specific contrast between the infarcted and normal areas of heart. To our knowledge, this is the first time that MnCO 3 -based nanoparticles were applied in vivo for detection of myocardial infarction by MRI.…”
Section: Introductionmentioning
confidence: 99%